STUDI KELENGKAPAN DOKUMENTASI SITUATION, BACKGROUND, ASSASSEMENT, RECOMMENDATION (SBAR) PADA FASE PASCA ANESTESI DI RS KHUSUS BEDAH JATIWINANGUN PURWOKERTO - Mutiara Fadilah, Rismi; Nova, Rahmaya; Heri Wibowo, Tophan (NHM PRESS, 2024)
SBAR communication technique is one of the communication techniques used when patients are immediately taken to the treatment room, both ordinary treatment rooms and intensive care. The purpose of this study was to determine the completeness of the Situation, Background, Assessment, Recommendation (SBAR) documentation in the post-anesthesia phase at Jatiwinangun Purwokerto Surgical Specialty Hospital. Descriptive quantitative research with a cross sectional approach. The sample in this study was 84 respondents. This research instrument is an observation sheet. The results showed that the situation documentation component in the post-anesthesia phase at Jatiwinangun Purwokerto Specialized Surgical Hospital was complete as many as 64 respondents (76.2%). The background documentation component in the post-anesthesia phase at Jatiwinangun Purwokerto Specialized Surgical Hospital was complete as many as 57 respondents (64.3%). The assessment documentation component in the post-anesthesia phase at Jatiwinangun Purwokerto Specialized Surgical Hospital was complete as many as 48 respondents (57.1%). The recommendation documentation component in the post-anesthesia phase at Jatiwinangun Purwokerto Specialized Surgical Hospital was complete as many as 72 respondents (85.7%). From these results it can be concluded that SBAR documentation at Jatiwinangun Specialized Surgical Hospital is said to be quite complete.